Peran Perpustakaan Digital Terhadap Minat Baca Mahasiswa - Afifatul Awalia; Sufia; Sya’dullo; Mashudi; Abd Wafi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article examines the role of digital libraries in increasing students' reading interest, especially in the context of the digital era full of information. This study uses a qualitative descriptive method with library research as the basis. The analysis was conducted by collecting information from various sources, including books, journal articles, and online sources, to explore the benefits and challenges of digital libraries in promoting reading interest. The results of the study indicate that digital libraries offer various advantages, such as easy access, diverse collections, advanced search features, and interactive features that support the reading experience. In addition, digital libraries play a role in improving digital literacy, facilitating collaboration and knowledge sharing, and encouraging a stronger reading culture among students. However, challenges such as limited internet access and difficulties in adapting to technology need to be overcome. In conclusion, digital libraries have great potential to increase students' reading interest and strengthen the quality of education. This study suggests the need for training and development programs to maximize the benefits of digital libraries and overcome existing challenges